The Optimization of Technical Assistance Activities for Local Supplementary Feeding as an Effort to Prevent Stunting in Toddlers at Latulip Posyandu, Kampung Manggis Community Health Center, Bogor - Syaripah, Rosita; Mulyati, Sri; Ayu, Nur Fitri; Marlina, Endah Dian; Lubis, Rosni (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Stunting is a condition of growth failure in children under the age of five caused by chronic malnutrition, especially during the first 1,000 days of life. Stunting is characterized by a child’s length or height being below the standard for their age. The government is making efforts to reduce the incidence of stunting through the provision of local supplementary feeding (PMT-Lokal). Objective: To reduce the incidence of stunting in toddlers through the provision of PMT-Lokal. Method: This program was carried out through several activities, including preparation and coordination with Posyandu cadres and technical assistance in the provision of PMT-Lokal. The activity was conducted on December 23–24, 2024, involving 36 toddlers, of whom 4 were identified as stunted. The implementation began with providing education to the cadres about PMT-Lokal and continued with direct assistance in its distribution. Conclusion: This community service activity was successfully implemented. Keywords: Assistance, Local Supplementary Feeding, Stunting